Epigenetic specifications of host chromosome docking sites for latent Epstein-Barr virus - Kyoung-Dong Kim (Nature Portfolio, 2020)
Epstein-Barr virus (EBV) episomes tether to the host chromosome via EBNA1. Here, using circular chromosome conformation capture (4C), Kim et al. identify attachment sites and show that EBV episomes preferentially associate with transcriptionally silenced genes in Burkitt lymphoma cells.